Soil Matrix Determines the Outcome of Interaction Between Mycorrhizal Symbiosis and Biochar for Andropogon gerardii Growth and Nutrition - Paymaneh, Zahra; Gryndler, Milan; Konvalinková, Tereza; Benada, Oldřich; Borovička, Jan; Bukovská, Petra; Püschel, David; Řezáčová, Veronika; Sarcheshmehpour, Mehdi; Jansa, Jan (Frontiers in Microbiology, 2018)
Biochar has been heralded as a multipurpose soil amendment to sustainably increase soil fertility and crop yields, affect soil hydraulic properties, reduce nutrient losses, and sequester carbon. Some of the most spectacular results of biochar (and organic nutrient) inputs are the terra preta soils in the Amazon, dark anthropogenic soils with extremely high fertility sustained over centuries. Such soil improvements have been particularly difficult to achieve on a short run, leading to speculations that biochar may need to age (weather) in soil to show its best. Further, interaction of biochar with arbuscular mycorrhizal fungi (AMF), important root symbionts of a great majority of terrestrial plants including most agricultural crops, remains little explored. To study the effect of aged biochar on highly mycotrophic Andropogon gerardii plants and their associated AMF, we made use of softwood biochar, collected from a historic charcoal burning site. This biochar (either untreated or chemically activated, the latter serving as a proxy for freshly prepared biochar) was added into two agricultural soils (acid or alkaline), and compared to soils without biochar. These treatments were further crossed with inoculation with a synthetic AMF community to address possible interactions between biochar and the AMF. Biochar application was generally detrimental for growth and mineral nutrition of our experimental plants, but had no effect on the extent of their root colonized by the AMF, nor did it affect composition of their root-borne AMF communities. In contrast, biochar affected development of two out of five AMF (Claroideoglomus and Funneliformis) in the soil. Establishment of symbiosis with AMF largely mitigated biochar-induced suppression of plant growth and mineral nutrition, mainly by improving plant acquisition of phosphorus. Both mycorrhizal and nonmycorrhizal plants grew well in the acid soil without biochar application, whereas nonmycorrhizal plants remained stunted in the alkaline soils under all situations (with or without biochar). These different and strong effects indicate that response of plants to biochar application are largely dependent on soil matrix and also on microbes such as AMF, and call for further research to enable qualified predictions of the effects of different biochar applications on field-grown crops and soil processes.